Sexual Functioning in Females with OCD: A Comparative Cross-sectional Study - Nirupama Jaiswal; Adarsh Tripathi; Bandna Gupta; Shweta Singh (Journal of Psychosexual Health)
Background: Clinical research and evidence are limited regarding sexual functioning in patients with obsessive-compulsive disorder (OCD) and the impact of pharmacological treatment on it. Aim: To study and compare sexual functioning in females among three groups viz. drug naïve symptomatic OCD cases (Group 1), OCD patients receiving pharmacological treatment, and in remission (Group 2), and age-matched healthy controls (Group 3). Method: Heterosexual sexually active females of 18 and 45 years with OCD seeking treatment at a tertiary care center in north India were assessed on the Relationship Assessment Scale (RAS), Female Sexual Functioning Index (FSFI), and Sexual Quality of Life-Female (SQOL). Results: The sample consisted of 150 subjects, (50 in each group). The majority of women were married, in the reproductive age group (18-45 years). The majority of women in Groups 1, 2, and 3 (84%, 74%, and 82%, respectively), were Hindus and homemakers. Most belonged to the nuclear family (58%, 52%, and 54% in Groups 1, 2, and 3, respectively) and were educated up to secondary school and monthly family income was comparable among the groups which were 10,000-20,000 in most of them (50%, 54%, and 50% in Group 1, 2, and 3, respectively). All the groups were homogeneous regarding socio-demographic variables. Sexual dysfunction (SD) was 68% in (Group 1) and (Group 2) and 28% in (Group 3) as per FSFI. There was no significant difference between Group 1 and Group 2. Subjects having symptoms in contamination and sexual domain had more dysfunction in desire, arousal, and satisfaction. Sexual functioning and SQOL were negatively correlated with the age and duration of illness Conclusion: SD is significantly higher in both drug naïve symptomatic OCD and pharmacologically treated patients in remission in comparison to healthy controls. There is no major difference in sexual functioning of drug naïve and adequately treated patients receiving pharmacotherapy and currently in remission.